A Load Modulated Balanced Amplifier for Telecom Applications - Quaglia, Roberto; Cripps, Steve (IEEE transactions on microwave theory and techniques, 2018)
This paper presents the design and characterization of a load modulated balanced amplifier for telecom base station applications adopting a novel mode of operation. The theory of operation is described explaining the main differences compared to Doherty amplifiers, in particular the RF bandwidth advantages and, on the other hand, the intrinsic nonlinear behavior. The specific design strategy that adopts prematching for back-off broadband matching is explained in detail. A prototype, based on 25-W GaN packaged devices, has been fabricated and measured with single tone CW and modulated signal stimulus. For CW conditions, on the 1.7-2.5-GHz band, the peak output power is between 63 and 78 W, with power added efficiency higher than 48%, 43%, and 39% at saturation, 6- and 8-dB output power back-off, respectively. With a modulated signal for Long Term Evolution the amplifier provides an average output power of around 10 W, with efficiency higher than 40%, and can be linearized by adopting a low complexity predistorter. If compared to previously published power amplifiers targeting similar power and bandwidth, the measurement shows very good performance, demonstrating the potential of this novel technique in the field of efficiency enhanced transmitters.